Cell site analysis; use and reliability of survey methods. (September 2021) - Tart, Matt; Brodie, Iain; Patrick-Gleed, Nicholas; Edwards, Brian; Weeks, Kevin; Moore, Robert; Haseler, Richard
Abstract: An RF Survey may form part of a wider forensic strategy. The purpose of a survey within this strategy, and the manner in which survey data may be used to better inform evaluative or investigative opinion, is discussed. Hazards of using survey results in isolation of other information to produce a series of piecemeal technical observations (in isolation of each other and the wider purpose of the examination) are explored. Technical issues concerning measuring a complex radio environment, and methods to address those issues, are presented. Experiments comparing CDR ("ground truth" data) from a known location is compared to survey measurements focussed on that location. The performance of methods using engineering handset survey devices (Anite Nemo) is compared with that of Software Controlled Radio (QRC ICS-500) for these trial data. Assessments of uncertainty within the methods tested are made, including accuracy, precision and reliability. Highlights: Types of survey, equipment and use of survey data to better inform findings are addressed. Technical assessment of reliability of survey methods is discussed. Network generated ("ground truth") call data made from a known location is compared to survey measurements.